Digital marketing strategies to meet digital consumers’ behavior in the new era - Natale Palmucci, Dario (Economic and business review, 2025)
This paper examines how digital marketing is being reshaped by five interrelated tensions: balancing data privacy and personalization; navigating global–local dynamics (including cultural sensitivities and country-of-origin effects); integrating artificial intelligence without losing human connection; ensuring authentic communication to mitigate reputational risks linked to environmental, social, and governance (ESG) and ethical storytelling; and responding to shifting consumer preferences, particularly among younger generations. We combine a targeted literature review with semistructured interviews of marketing professionals across industries and seniority levels. Findings portray marketers as “tightrope walkers” who negotiate paradoxes that redefine the function. We propose an integrated framework that synthesizes previously fragmented strands into a coherent structure and reconceptualizes these tensions as structuring logics rather than contextual challenges. We also identify the governance conditions that make them workable in practice—trust-based data ecosystems, context-conditioned glocal capabilities, human-in-the-loop AI, and evidence-bearing ESG communication. Managerially, the framework offers a roadmap to balance agility with coherence, data with empathy, and innovation with trust. Limitations stem from the qualitative, practitioner-focused design; future research should incorporate consumer data, quantitative tests, and cross-industry comparisons to assess boundary conditions and generalizability.
Keywords: consumer behaviour; electronic marketing; elektronsko trženje; marketing; trženje; vedenje potrošnikov